Probing the structure of the human immunodeficiency virus surface glycoprotein gp120 with a panel of monoclonal antibodies. - Moore, J P (1994)
We have probed the structures of monomeric and oligomeric gp120 glycoproteins from the LAI isolate of human immunodeficiency virus type 1 (HIV-1) with a panel of monoclonal antibodies (MAbs); most of these MAbs are directed against continuous epitopes. On native monomeric gp120, most of the first conserved (C1) domain is accessible to MAbs, although some regions of C1 are relatively inaccessible. All of the MAbs directed against the C2, C3, and C5 domains bind preferentially to denatured monomeric gp120, indicating that these regions of gp120 are poorly accessible on the native monomer, although the extreme C terminus in C5 is well exposed. Segments of the V1, V2, and V3 loops are exposed on the surface of monomeric gp120, although the base of the V3 loop is inaccessible. A portion of C4 is also available for MAb binding on monomeric gp120, as is the extreme C terminus in C5. However, on oligomeric gp120-gp41 complexes, only the V2 and V3 loops (and perhaps V1) are well exposed and a segment of the C4 region is partially exposed; continuous epitopes in C1 and C5 that are accessible to antibodies on monomeric gp120 are occluded on the oligomer. Although deletion of the V1, V2, and V3 loops resulted in increased exposure of several discontinuous epitopes overlapping the CD4-binding site, the exposure of most continuous epitopes on the monomeric gp120 glycoprotein was not affected. These results imply a HIV-1 gp120 structure in which the conserved continuous determinants are inaccessible; in some cases, this inaccessibility is due to intramolecular interactions between conserved regions, and in other cases, it is due to intermolecular interactions with other components of the glycoprotein spike. These findings have implications for the design of subunit vaccines based on gp120.